Phytochemical composition and in vitro antioxidant activity of methanolic and aqueous extracts of aerial part of Pentatropis nivalis(Asclepiadaceae) - Nilesh P. Babre; T. Shivraj Gouda; Narayanswamy Lachmanan Gowrishankar (International Journal of Phytomedicine, 2018)
The objective of present study was to evaluate preliminary phytoconstitutents and invitro antioxidant potential of Pentatropis nivalis (Asclepiadaceae). During the preliminary phytochemical analysis, methanolic and aqueous extracts of aerial part of Pentatropis nivalis was screened for the presence of phenolic, saponins, flavonoids, alkaloids, tannins and phytosterols. TLC of extracts were performed by using various solvent systems. Phytochemicals screening and TLC spots of MEPN and AEPN showed the presence of glycoside, steroids, terpenoids, phenolic, saponins, Methanolic extract showed better qualitative tests for presence of secondary metabolites than aqueous extract.The in-vitro antioxidant potential of extracts were evaluated by DPPH and FRAP, and both methods showed that the plant possesses good antioxidant activity.